Behavioral Economics and Decision Making: Understanding Irrationality and Biases in Economic Choices - Liestyowati, Liestyowati (Economics Studies and Banking Journal (DEMAND), 2024)
This research investigates the relationship between Behavioral Economics and economic decision making, with a focus on understanding the impact of emotions, cognitive factors, motivation, and level of self-control on individual economic decisions. Through a systematic literature review approach, this study presents a hypothesis which suggests that various psychological factors significantly influence economic decision making. These findings have important implications for our understanding of consumer behavior and decision-making processes in an economic context, and offer a more holistic view in designing more effective policies and strategies in promoting healthy economic behavior.